1988
DOI: 10.1007/bf00176837
|View full text |Cite
|
Sign up to set email alerts
|

Is the forced swimming test a suitable model for revealing antidepressant activity?

Abstract: The forced swimming test is reviewed. This test appears to be suitable for detecting antidepressant activity in rats but not in mice. Difference in experimental procedure may account for the different sensitivity to drugs of the two animal species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
479
0
7

Year Published

1998
1998
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 951 publications
(513 citation statements)
references
References 95 publications
(153 reference statements)
27
479
0
7
Order By: Relevance
“…In both experimental paradigms, the animal is subjected to an inescapable stress and typically responds with alternating bouts of escape-oriented behavior and immobility. All major classes of ADs effectively reduce immobility in both tests, confirming their validity as drugscreening paradigms (Borsini and Meli, 1988;Cryan et al, 2005a;Petit-Demouliere et al, 2005;Porsolt, 2000;Steru et al, 1985). Drugs in both experimental paradigms are typically administered acutely.…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…In both experimental paradigms, the animal is subjected to an inescapable stress and typically responds with alternating bouts of escape-oriented behavior and immobility. All major classes of ADs effectively reduce immobility in both tests, confirming their validity as drugscreening paradigms (Borsini and Meli, 1988;Cryan et al, 2005a;Petit-Demouliere et al, 2005;Porsolt, 2000;Steru et al, 1985). Drugs in both experimental paradigms are typically administered acutely.…”
Section: Introductionmentioning
confidence: 62%
“…Drugs in both experimental paradigms are typically administered acutely. However, some studies have shown that subchronic or acute effects were increased by chronic pre-administration of the AD (Borsini and Meli, 1988;Conti et al, 2002;Dulawa et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the FST does represent an acute stressful event, since it is associated with a profound increase in adrenocorticotropin and corticosterone levels (Bilang-Bleuel et al, 2002;Rittenhouse et al, 2002), as well as with neurochemical and morphological changes in the hippocampus (Bilang-Bleuel et al, 2005) and prefrontal cortex (Izquierdo et al, 2006). Importantly, the immobility response in the FST can be prevented by glucocorticoid antagonists (Jefferys and Funder, 1987;Korte et al, 1996;Bilang-Bleuel et al, 2005) and various types of antidepressant treatments, including tricyclic antidepressants, monoamine oxidase inhibitors, SSRIs, and NA reuptake inhibitors (see Borsini and Meli, 1988).…”
Section: Depression-like Behavior In Rats and The Fstmentioning
confidence: 99%
“…However, this animal model also has some drawbacks represented by the possibility to obtain some false positives or negatives. Drugs enhancing motor activity, such as anticholinergics and antihistamines, may give a ''false'' positive effect in the forced swimming test and antidepressants such as bupropion, nomifensine and amineptine would then be rejected since they increase motor activity (Borsini and Meli, 1988). Cytosolic Ca 2C regulates numerous neuronal functions (Berridge, 1998) and, therefore, a variation of intracellular Ca 2C contents can induce behavioural side effects.…”
Section: Discussionmentioning
confidence: 99%